Recovery of latent fingermarks on metal part of motorcycle submerged in different aquatic environments - Nur Fatin Nabihah Said; Nur Sharida Abd Rahman; Puwira Jaya Othman; Yusmazura Zakaria; Nik Fakhuruddin Nik Hassan (Penerbit Universiti Kebangsaan Malaysia, 2021)
Motorcycle theft cases in Malaysia have increased quite significantly with more motorcycles were reported stolen every day. In many cases, criminals had removed the components they only required and disposed the remaining parts into various sources of water. Unfortunately, the evidence recovered underwater was thought not to have forensic value with regards to fingermark recovery. This study aimed to determine the survivability of the latent fingermarks submerged in various water environments. Latent fingermarks were deposited on metal parts of motorcycle and submerged into four aquatic environments; river, lake, mine, and tap water for two weeks with time intervals for collection of 1, 8, 24, 48, 96, 168, and 336 h. Upon recovery, the fingermark samples were developed using Small Particle Reagent (SPR). The developed fingermarks were assessed using Biometric Fingerprint Identification System (BIOFIS). The persistence of fingermarks immersed in tap water was found to last up to more than two weeks. Contrarily, fingermark in other water environments can only survive up to 96 h after being submerged. The fingermarks submerged in the lake appeared to be better preserved as compared to those submerged in the river and mine. The development of underwater fingermarks is still feasible, and identifiable fingermarks can still be recovered at the early submersion period.